2019
DOI: 10.1123/jtpe.2018-0282
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Scale Assessing Test Anxiety in Physical Education

Abstract: Purpose: There is currently no scale assessing test anxiety in physical education (PE), despite the specificities of this class (e.g., body image, failure in front of peers). Accordingly, the aim of the present study was to develop a specific scale named the “Revised Test Anxiety and Regulatory Dimension of Anxiety in Physical Education” (RTAR-PE). Method: Self-report data were collected from 281 (Study 1) and 390 (Study 2) students in French schools (age range: 13–18 years). Results: Study 1 showed that the R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 35 publications
(66 reference statements)
3
20
0
Order By: Relevance
“…Test anxiety. Test anxiety was assessed with the RTAR-PE scale (Danthony et al, 2019). Four items assessed the worry dimension of PE test anxiety (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Test anxiety. Test anxiety was assessed with the RTAR-PE scale (Danthony et al, 2019). Four items assessed the worry dimension of PE test anxiety (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Mastery-avoidance goals were positively correlated with worry and somatic tension (Putwain et al, 2010;Putwain and Symes, 2012), performance-approach goals were positively related to bodily symptoms (Putwain et al, 2010), and performanceavoidance goals were positively related to worry and somatic tension (Putwain and Symes, 2012). The only study (Danthony et al, 2019) assessing test anxiety in PE and achievement goals showed that approach-based goals were negatively correlated with worry and self-focus, and positively correlated with perceived control. Mastery-approach goals were negatively correlated with bodily symptoms, while performance-approach goals were negatively correlated with somatic tension.…”
Section: Test Anxiety and Achievement Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, according to a current meta-analytic review, test anxiety is more prevalent among middle school students (Von der Embse, Jester, Roy & Post, 2018). In terms of gender, it has been shown that females have higher levels of test anxiety than males (Arnold, 2002;Núñez-Peñaa, Suárez-Pellicioni, & Bono, 2016;Ely & Jastrowski-Mano, 2019;Danthony, Mascret, & Cury, 2019). A study conducted among elementary school children concluded that central exams are more anxiety-provoking than classroom testing (Segool, Carlson, Goforth, von der Embse, & Barterian, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This situation is similar in physical education and sport courses and measuring this exam anxiety level seems important. The purpose of this study was to adapt the physical education and sport course exam anxiety scale developed by Danthony, Mascret and Cury (2019) to Turkish context. Adaptation process of the scale was executed by two language experts.…”
mentioning
confidence: 99%